2012
DOI: 10.4238/2012.october.17.3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of synonymous codon usage bias in the model grass Brachypodium distachyon

Abstract: ABSTRACT. Brachypodium distachyon has been proposed as a new model for the temperate grass because it is related to the major cereal grain species (such as wheat, barley, oat, maize, rice, and sorghum) and many forage and turf species. In this study, a multivariate statistical analysis was performed to investigate the characteristics of codon bias and the main factors affecting synonymous codon usage in Brachypodium. We found that lowand high-GC content genes with different codon usage occur frequently in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 37 publications
(56 reference statements)
2
25
0
Order By: Relevance
“…Although a small number of genes distributed in the vicinity of the expected curve, indicated that compositional constraint was the only determinant factor shaping the codon usage pattern. A majority of genes with low ENC values deviated well below the expected curve, indicating that GC3s value was a major determinant of codon usage bias and that other factors independent of nucleotide composition shaped codon usage as well [65]. Consequently, the codon usage pattern of genes in the four cotton genomes and the four subgenomes might be shaped by the combined effects of directional mutation and neutral selection.…”
Section: Enc and Gc3s Scatter Plot (Enc-plot)mentioning
confidence: 88%
“…Although a small number of genes distributed in the vicinity of the expected curve, indicated that compositional constraint was the only determinant factor shaping the codon usage pattern. A majority of genes with low ENC values deviated well below the expected curve, indicating that GC3s value was a major determinant of codon usage bias and that other factors independent of nucleotide composition shaped codon usage as well [65]. Consequently, the codon usage pattern of genes in the four cotton genomes and the four subgenomes might be shaped by the combined effects of directional mutation and neutral selection.…”
Section: Enc and Gc3s Scatter Plot (Enc-plot)mentioning
confidence: 88%
“…If the distribution of the plotted genes is below the curve, then the codon usage bias is assumed to be affected by selection and other factors (Liu et al, 2012).…”
Section: Enc-gc3 Plotmentioning
confidence: 99%
“…We found a reasonable pattern of evolutionary relationships between the LjNBS genes. Most researchers have identified two clades of NBS genes in dicots, TIR-type and non-TIR-type genes (Liu et al, 2012). However, research in monocots has been unable to resolve relationships among NBS domain sequences, and has yielded a star-like topology (Cheng et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The average GC3s value was 0.38, indicating a high frequency of AT in LjNBS gene sequences at the third position. Reduced selection against mutations in plant genomes could lead to a wide distribution bias of GC3s values (Liu et al, 2012). In LjNBS genes, the GC3s values ranged from 0.29 to 0.54, suggesting that LjNBS genes underwent mutation pressure or selection against mutation.…”
Section: Codon Usage Bias In L Japonicus Nbs-encoding Genesmentioning
confidence: 99%